Design and synthesis of extended quinoxaline derivatives and their charge transport properties. Issue 102 (20th October 2016) - Yang, Junwei; Zhu, Haoyun; Huang, Yuli; Huang, Wei; Wang, Weizhi
Abstract : A scalable and convenient strategy is described to synthesize extended conjugation quinoxaline derivatives from phenylene-ethynylene arrays. The fabricated FET devices possess good performance, with mobilities of 0.47 cm 2 V −1 s −1 and 0.99 cm 2 V −1 s −1 . Abstract : A scalable and convenient strategy is described to synthesize extended conjugation quinoxaline derivatives from phenylene-ethynylene arrays. By tuning the solvent, the compounds display bright emission solvatochromism. Furthermore, the fabricated FET devices possess good performance characteristics, with mobilities of 0.47 cm 2 V −1 s −1 and 0.99 cm 2 V −1 s −1 . The mobilities are higher than those of corresponding to the alkyl substituted compounds, which can be proven by grazing incidence X-ray diffraction (GIXRD) measurement.